Exploring the acceptance of ChatGPT as a learning tool among academicians: a qualitative study - Muaadh Mukred; Umi Asma’ Mokhtar; Burkan Hawash (Penerbit Universiti Kebangsaan Malaysia, 2023)
This qualitative study aims to examine the ChatGPT acceptance as a learning tool for academics by identifying factors influencing its acceptance and adoption. In academia, an exciting development is the significant attention directed toward ChatGPT, an AI-based conversational agent, as a potential learning. Nevertheless, more knowledge and information are needed concerning the determinants of its acceptance and use among academics. This study answers the need by conducting semi-structured interviews with ten academics from different disciplines and academic levels, selected through purposive sampling. Following the interview sessions, the interviews were transcribed and analysed using thematic analysis to highlight major themes and patterns. Based on the findings obtained, the academics displayed positive attitudes towards adopting ChatGPT as a learning tool, which holds the potential to resolve challenges faced during the system's teaching and learning process. The significant factors influencing ChatGPT acceptance and use are perceived usefulness, ease of use, credibility, and compatibility with the current teaching and learning methods. Additionally, the prior experience of academics with using AI-based tools and their proficiency in their use have a key role in their ChatGPT acceptance and adoption. The significant contribution of this study to literature is related to the adoption of AI-based tools in the field of academics and the determination of the factors that influence ChatGPT adoption and use for learning. Practically, the study also contributes to educational institutions and developers by providing a guideline for effective ChatGPT design and implementation for optimum potential and enhancement of the teaching and learning experience within academia.